Respuesta :

Answer:

[tex]\frac{F_{f}}{m*g*cos(x)} =u[/tex]

Step-by-step explanation:

The statement says the following:

[tex]F_{f}= u*F_{N} \\F_{N}=m*g*Cos(∅)[/tex]

We need to find 'u' given that we know the following terms:[tex]F_{f}, F_{N}[/tex], m, g, ∅

The way to do that is to substitute not known expression into known expression,  we will use the expression of [tex]F_{N}[/tex] in [tex]F_{F}[/tex]

This leads to

[tex]F_{f}=u*m*g*cos(∅)[/tex]

Finally we can obtain 'u' by dividing the whole equation with the terms that are with 'u'

We have this

[tex]\frac{F_{f}}{m*g*cos(x)} =u[/tex]

Where 'u' is the variable that you are  looking for